Phthiriasis palpebrarum: a diagnosis of keen observation and suspicion - Sivasubramanian, Muthu Bharathi; Ramakrishnan, Ramachandran; Narasimhan, Murali (International Journal of Research in Dermatology, 2020)
Phthiriasis palpebrarum is a rare cause of eyelid infestation and it mimics seborrheic blepharitis. A 60 years old female presented with itching in the eyelids and scalp. On initial examination scaling was present in her eyelashes and eyelid margin. On further examination some movements were noticed in her eyelashes. Immediately, dermatoscopic examination was done and was found to have multiple nits and multiple crab lice over her eyelashes. She was treated with oral ivermectin and trimming of eyelashes as advised by ophthalmologist. She improved in a week. Thus, phthiriasis palpebrarum can mimick seborrheic blepharitis and therefore high index of suspicion and detailed examination is necessary for appropriate diagnosis.